PENGARUH METODE CERAMAH DAN DISKUSI INTERAKTIF DALAM PEMBELAJARAN TASAWUF MAHASISWA PAI UNIVERSITAS SUNAN GIRI SURABAYA - Aini, Nurul; Shobri, Jami'; Ghozali, Solchan (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
This study aims to examine the effectiveness of lecture and interactive discussion methods in improving students’ understanding of Sufism learning in the Islamic Religious Education (PAI) study program. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group model involving 60 students divided into an experimental group and a control group. Data were collected through pretest-posttest assessments, student response questionnaires, and classroom participation observations. The data were analyzed using independent sample t-test, N-Gain analysis, and effect size measurement. The findings indicate that the interactive discussion method produced a higher improvement in students’ learning outcomes compared to the lecture method, as reflected by the posttest mean score increase of 16.8 points with an N-Gain value of 0.56 (high category), while the lecture method showed an increase of 7.8 points with an N-Gain value of 0.32 (moderate category). Statistical testing confirmed a significant difference between the two groups (p < 0.05). The results demonstrate that interactive discussion promotes active participation and facilitates deeper conceptual and spiritual understanding in Sufism learning. This study implies that participatory learning approaches are essential for enhancing holistic learning outcomes in Islamic higher education.